Triaryl carbonium ion-pair-mediated cooperative aerobic dehydrogenation of N-heterocycles - Zhang, Zhenguo (2023)
The triphenylmethyl radical was discovered by Gomberg in 1900 and has been shown to be a persistent radical species. Surprisingly, this radical is rarely used in organic synthesis since its discovery over a century ago. Here, we report a metal-free aerobic dehydrogenation of N-heterocycles mediated by a triphenylmethyl radical generated from a triaryl carbonium ion pair as the precatalyst in the presence of TEMPO. This protocol exhibits a broad substrate scope and excellent functional group tolerance. The practicality has also been demonstrated with the gram-scale preparation of key intermediates of small-molecule drugs and late-stage functionalization of various dipine drugs. Mechanistic studies and DFT calculations revealed that the triphenylmethyl radical was involved in the catalytic cycle and was essential for the aerobic dehydrogenation process.